An interactive fuzzy satisficing method for multiobjective integer programming problems through genetic algorithms - Sakawa, M.; Shibano, T.; Kato, K. (1998 Second International Conference on Knowledge-Based Intelligent Engineering Systems Proceedings, 1998)
This paper deals with multiobjective integer programming problems by considering fuzzy goals of the decision maker for objective functions. After determining the fuzzy goals of the decision maker, if the decision maker specifies the reference membership values, the corresponding Pareto optimal solution can be obtained by solving the augmented minimax problem which becomes an integer programming problem. For solving the problem, decoding algorithms for 0-1 programming problems are revised and ringed double strings are also introduced. Then an interactive fuzzy satisficing method is presented together with an illustrative numerical example.